2009
DOI: 10.1063/1.3179147
|View full text |Cite
|
Sign up to set email alerts
|

Spin reorientation transitions in Pt/Co/Pt films under low dose Ga+ ion irradiation

Abstract: An elegant route for tuning the magnetic anisotropy of ultrathin Co films by Ga+ ion irradiation is presented. The magnetic anisotropy of a Pt/Co(2.6 nm)/Pt film is first changed from in-plane to out-of-plane by uniform low dose Ga+ ion irradiation at 30 keV. When increasing the dose, a second spin reorientation transition toward the sample plane is also evidenced. This could be a way to design magnetic nanowires with perpendicular anisotropy, embedded in an in-plane magnetized environment, either by irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 21 publications
4
24
0
Order By: Relevance
“…The effects on the magnetic properties of CoPt as functions of the platinum content have been studied extensively, both theoretically [3] and experimentally [4,5]. Moreover, in recent experimental work [6] it was demonstrated that the magnetocrystalline anisotropy energy (MAE) of cobalt can be tuned by letting platinum impurities migrate into the cobalt system. Generally it is agreed that the addition of platinum to a magnetic material, such as Fe or Co, influences the magnetic properties, in particular, the MAE of the material primarily through the strong spin-orbit coupling of Pt [7].…”
Section: Introductionmentioning
confidence: 99%
“…The effects on the magnetic properties of CoPt as functions of the platinum content have been studied extensively, both theoretically [3] and experimentally [4,5]. Moreover, in recent experimental work [6] it was demonstrated that the magnetocrystalline anisotropy energy (MAE) of cobalt can be tuned by letting platinum impurities migrate into the cobalt system. Generally it is agreed that the addition of platinum to a magnetic material, such as Fe or Co, influences the magnetic properties, in particular, the MAE of the material primarily through the strong spin-orbit coupling of Pt [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the quasi-uniform mode, the FIB is rapidly scanned over all the investigated film area. Some preliminary results were reported for sputtered Co (d Co = 1.4 nm) [13,29] and Co (d Co = 2.6 nm) [16] films. We evidenced rather similar magnetic changes by both irradiation procedures at comparable estimated fluences while the incoming Ga + ion rate in a nanosize region is much higher for the FIB procedure than for uniform irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported [13], the as-grown Pt/Co(1.4 nm)/Pt sputtered film (d Co < d SRT ), exhibits a square magnetic hysteresis loop at room temperature consistent with a rather large anisotropy field H ef f A = 1.9 kOe. On the contrary, for thicker Co layers (d Co > d SRT ) with in-plane anisotropy, d Co = 2.6 nm [16] or d Co = 3.0 nm (Fig. 2a), a pure S-shape field induced magnetization curve without hysteresis and with high saturation field was measured.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations